Principal component analysis of synaptic density measured with [11C]UCB-J PET in early Alzheimer’s disease - O'Dell, Ryan S.; Higgins-Chen, Albert; Gupta, Dhruva; Chen, Ming-Kai; Naganawa, Mika; Toyonaga, Takuya; Lu, Yihuan; Ni, Gessica; Chupak, Anna; Zhao, Wenzhen; Salardini, Elaheh; Nabulsi, Nabeel B.; et al. (NeuroImage clinical, 2023)
•This is the first application of PCA to synaptic density PET in Alzheimer’s disease.•Principal components reflect spatial patterns of covariance in synaptic density.•Principal components are correlated with unique characteristics in Alzheimer’s disease.•These findings support synaptic density as a robust biomarker of disease severity. Synaptic loss is considered an early pathological event and major structural correlate of cognitive impairment in Alzheimer’s disease (AD). We used principal component analysis (PCA) to identify regional patterns of covariance in synaptic density using [11C]UCB-J PET and assessed the association between principal components (PC) subject scores with cognitive performance. [11C]UCB-J binding was measured in 45 amyloid + participants with AD and 19 amyloid– cognitively normal participants aged 55–85. A validated neuropsychological battery assessed performance across five cognitive domains. PCA was applied to the pooled sample using distribution volume ratios (DVR) standardized (z-scored) by region from 42 bilateral regions of interest (ROI). Parallel analysis determined three significant PCs explaining 70.2% of the total variance. PC1 was characterized by positive loadings with similar contributions across the majority of ROIs. PC2 was characterized by positive and negative loadings with strongest contributions from subcortical and parietooccipital cortical regions, respectively, while PC3 was characterized by positive and negative loadings with strongest contributions from rostral and caudal cortical regions, respectively. Within the AD group, PC1 subject scores were positively correlated with performance across all cognitive domains (Pearson r = 0.24–0.40, P = 0.06–0.006), PC2 subject scores were inversely correlated with age (Pearson r = -0.45, P = 0.002) and PC3 subject scores were significantly correlated with CDR-sb (Pearson r = 0.46, P = 0.04). No significant correlations were observed between cognitive performance and PC subject scores in CN participants. This data-driven approach defined specific spatial patterns of synaptic density correlated with unique participant characteristics within the AD group. Our findings reinforce synaptic density as a robust biomarker of disease presence and severity in the early stages of AD.